(untitled) (Research, Society and Development, 2025)
Missioneira-gigante [Axonopus jesuiticus (Araújo) Valls x Axonopus scoparius (Flüggé) Kuhlm.] is a forage species native to Santa Catarina and used in pasture-based production systems for feeding animals in southern Brazil. The leaf anatomy of grasses influences their nutritional value, especially the proportion of lignified tissues. The objective of this work was to describe aspects of leaf anatomy considering the proportion of tissues, and to evaluate the phenotypic plasticity of three genotypes of the species. Permanent slides were prepared from leaves of the triploid genotypes V14337 and SCS315 ‘Catarina Gigante’ (2n=3x=30) and the hexaploid genotype E401 (2n=6x=60). Vascular bundles in the leaf can be of three sizes, containing subepidermal sclerenchyma or not, in “I-girder” and “T-girder” arrangements. Vascular bundles of all sizes present a chlorophyllic parenchyma sheath in radial arrangement. The greatest phenotypic plasticity was observed in the proportion of sclerenchyma. Among the evaluated characters, the forage species presents low plasticity.